ANALISIS FAKTOR-FAKTOR PENERIMAAN APLIKASI SISTEM AUDIT AUDIT TOOL AND LINKED ARCHIVE SYSTEM (ATLAS) (Studi Empiris pada Kantor Akuntan Publik di Jawa Timur) - SE, Tatsuya Akashi (Jurnal Ilmiah Mahasiswa FEB, 2020)
The purpose of this study was to explore the influence of task-technology fit, perceived usefulness, perceived ease of use, auditor’s attitude, subjective norm, and perceived behaviour control on auditor’s behavioural intention to use ATLAS audit tool. The object of this study is the auditor who works at public accounting firm that operate using the ATLAS application in East Java. The data are obtained by using purposive sampling method with judgement sampling model and questionnaires as a survey to collect data from respondents. There are 60 questionnaires or 65.93 per cent of the number of questionnaires were distributed are obtained. The data was analysed with Partial Least Square method by SmartPLS application. The results show that perceived usefulness, auditor’s attitude, and subjective norm have positive and significant effects on auditor’s behavioural intention to use ATLAS application. Task-technology fit and perceived usefulness have positive and significant effects on auditor’s attitude. Auditor’s behavioural intention have negative and do not have a significant effect on perceived behavioural control and auditor’s attitude have positive and do not have significant effects on perceived ease of use. Key Word: ATLAS, Task-Technology Fit, Perceived Usefulness, Perceived Ease of Use, Auditor’s Attitude, Subjective Norm, Perceived Behaviour Control, and Auditor’s Intention